KAJIAN ETNOASTRONOMI DALAM KOSMOLOGI KEPERCAYAAN ALUK TO DOLO DI TANA TORAJA - Farid, Firdaus; Rofiuddin, Ahmad Adib (ELFALAKY: Jurnal Ilmu Falak, 2024)
This research examines ethnoastronomy in the context of the cosmology of Aluk ToDolo belief in Tana Toraja. Aluk Todolo is a traditional belief system of the Toraja people that has a close relationship with astronomical symbols and cosmology. This research aims to explore how the people of Tana Toraja utilize ethnoastronomical knowledge in the cosmological belief system of Aluk To Dolo and how this affects their traditional rites, ceremonies and social structures. The research method involved literature analysis, interviews with traditional leaders, and qualitative descriptive participatory observation using socio-historical, ethnological, and anthropological approaches and data collection was obtained from the review of textual studies. The results show that the elements of Ethnoastronomy in the Cosmology of Alok ToDolo belief are symbolized in the mapping of the universe in horizontal and vertical forms. The vertical form here is interpreted in the “four cardinal directions”, while the vertical mapping of the universe means that the universe consists of several layers.